OS CONFLITOS AGRÁRIOS NAS PÁGINAS DE A TRIBUNA: A DISPUTA TERRITORIAL ENTRE QUILOMBOLAS E O AGRONEGÓCIO DO EUCALIPTO NO NORTE DO ESPÍRITO SANTO - Gomes, Nathalia Esteves da Silva (2020)
This work presents an investigation about the representation of agricultural conflicts in the pages of the newspaper A Tribuna, focusing on territorial disputes between quilombola communities and international eucalyptus agribusiness, in the Northern Regi